Preparation and Quality Evaluation of Mozzarella Cheese from Different Milk Sources - Bhattarai, Rewati Raman; Acharya, Pushpa Prasad (2013)
Three mozzarella cheeses were prepared from three different milk sources i.e. cow (C), buffalo (B) and their mix (A) milks using DL (Streptococcus lactis and cremoris; S. Diacetalactic, Leuconostoc cremoris) and yoghurt cultures. Milk was standardized to C/F: 0.90/0.92 and process optimized for using all milk sources. The samples were analyzed for physico-chemical and functional properties, sensory attributes and protein and fat losses. Except ash and yield at 50% moisture; fat, protein, actual yield, pH, acidity and moisture were significantly influenced by milk sources. From sensory result, cow and mix cheeses were significantly superior, whereas functional properties were superior for cow cheese but buffalo and mix cheeses had higher nutritive value. From overall comparison, cow mozzarella cheese was ranked most suitable for pizza topping.